2010
DOI: 10.1097/fbp.0b013e32833470bd
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation increases morphine intake: behavioral and psychopharmacological aspects

Abstract: Environmental and situational factors are important determinants of recreational drug use in humans. We aimed to develop a reliable animal model for studying the effects of environmental variables on drug-seeking behavior using the 'social isolation/social restriction' paradigm. Adult Wistar rats housed in short-term isolation (21 days) consumed significantly more morphine solution (0.5 mg/ml) than rats living in pairs, both in one-bottle and in two-bottle tests. No differences were found in their water consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 62 publications
0
44
0
Order By: Relevance
“…The findings from these studies are complicated by several factors including strain, age, length of isolation, and whether or not the housing conditions remain the same throughout the experiment or are changed during the course of the experiment. Rodents housed in isolation have been found to consume more ethanol (Deatherage 1972; Ehlers et al 2007; Juarez and Vazquez-Cortes 2003; Parker and Radow 1974; Wolffgramm and Heyne 1991; Yanai and Ginsburg 1976) and morphine (Raz and Berger 2010) compared to social housed rodents; however, other studies find the opposite with isolated rodents consuming less ethanol (Anacker et al 2011a; Doremus et al 2005; Thorsell et al 2005) and cocaine (Smith 2012) compared to social housed rodents, as well as other studies the found no difference in consumption between isolated and social-housed groups (Deatherage 1972; Kulkosky et al 1980; Schenk et al 1990). …”
Section: Social Experiences Occurring Within the Drug Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings from these studies are complicated by several factors including strain, age, length of isolation, and whether or not the housing conditions remain the same throughout the experiment or are changed during the course of the experiment. Rodents housed in isolation have been found to consume more ethanol (Deatherage 1972; Ehlers et al 2007; Juarez and Vazquez-Cortes 2003; Parker and Radow 1974; Wolffgramm and Heyne 1991; Yanai and Ginsburg 1976) and morphine (Raz and Berger 2010) compared to social housed rodents; however, other studies find the opposite with isolated rodents consuming less ethanol (Anacker et al 2011a; Doremus et al 2005; Thorsell et al 2005) and cocaine (Smith 2012) compared to social housed rodents, as well as other studies the found no difference in consumption between isolated and social-housed groups (Deatherage 1972; Kulkosky et al 1980; Schenk et al 1990). …”
Section: Social Experiences Occurring Within the Drug Contextmentioning
confidence: 99%
“…For instance, Raz and Berger (2010) have demonstrated that isolation increases oral consumption of morphine relative to social housing. In addition, when rats in this study were switched from social housing to isolation housing, they exhibited an increase in morphine consumption.…”
Section: Social Experiences Occurring Within the Drug Contextmentioning
confidence: 99%
“…Social interactions additionally enhance the rewarding effects of cocaine (Thiel et al ., 2008) and morphine (Cole et al ., 2013) in laboratory rodents. There is also robust evidence that chronic social isolation of laboratory rodents increases responsiveness to, intake of, and preference for drugs of abuse (e.g., Zimmerberg & Brett; 1992; Phillips et al ., 1994; Raz and Berger, 2010; Cain et al ., 2012; Westenbroek et al ., 2013; Whitaker et al ., 2013; Meyer & Bardo, 2015; Yorgason et al ., 2016). …”
Section: Introductionmentioning
confidence: 99%
“…A follow-up study demonstrated the importance of social housing during development, in that rats reared in isolation but tested in social conditions showed greater levels of morphine consumption than rats reared and tested in social conditions (Alexander et al, 1981). Later studies extended these findings across a range of morphine concentrations and found that a period of social interaction prior to testing reduced consumption in the isolated subjects (Hadaway et al, 1979; Raz and Berger, 2010b). Further, a recent study indicated that daily treatment with fluoxetine attenuated, whereas daily treatment with parachlorophenylalanine (a serotonin synthesis blocker) enhanced, the increased morphine consumption in isolated rats (Raz and Berger, 2010a).…”
Section: Effects Of the Presence Of A Social Peermentioning
confidence: 84%